Advertisement Remove all ads

Evaluate: (2x – 5y)(2x + 3y) for X = 2 and Y = 3. - Mathematics

Sum

Evaluate: (2x – 5y)(2x + 3y) for x = 2 and y = 3.

Advertisement Remove all ads

Solution

(2x – 5y) (2x + 3y)

= 2x × 2x − 5y × 2x + 2x × 3y − 5y × 3y

= 4x2 − 10xy + 6xy − 15y2

Hence, x = 2 and y = 3

4x2 − 10xy + 6xy − 15y2

= 4(2)2 − 10(2)(3) + 6(2)(3) − 15(3)2

= 16 − 60 + 36 − 135

= 52 − 195

= −143

Concept: Multiplying a Polynomial by a Polynomial
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 11 Algebraic Expressions
Exercise 11 (C) | Q 11.2 | Page 143
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×